Cryptic species of black flies (Diptera: Simuliidae) at high elevations in the Oriental Region: The Simulium vernum species group in Thailand - Peter H. Adler (2020)
© 2020 Elsevier B.V. High-mountain summits in tropical regions are habitat islands that provide refugia for northern taxa and opportunities for speciation. These focal hotspots of biodiversity are also threatened by increasing anthropogenic pressures and changing climatic conditions. The largest species group of black flies, the Simulium vernum group, reaches its southern limit in the mountains of Southeast Asia, providing an opportunity to examine macrogenetic diversification at the southern edge of the group's range. We investigated the polytene chromosomes of two morphologically similar species in the S. vernum group, S. chomthongense Takaoka, Srisuka & Choochote, and S. khunklangense Takaoka & Srisuka, from their type localities near the summit of Doi Inthanon, Thailand's highest mountain. Chromosomal analyses of 112 larvae demonstrated reproductive isolation between S. chomthongense and S. khunklangense and revealed a cryptic species of S. chomthongense. The three species have the same fixed banding sequence in five of the six chromosome arms, but they are distinguished by the successive addition of overlapping inversions in the IIIL arm. The two cytospecies (A and B) of S. chomthongense s. l. are the third example of endemic or nearly endemic cryptic species pairs near the top of Doi Inthanon, suggesting the possibility of sympatric speciation and the importance of conserving high-elevation stream habitats.